The Effectiveness of Implementing Personal Storytelling on Students' Academic Achievement and Learning Motivation - Krisna Wijaya; Rozanah Katrina Herda; Sheikha Majid (Universitas Sarjanawiyata Tamansiswa, 2024)
In language learning contexts, conventional methods frequently fail to engage students meaningfully, making it difficult to improve their academic achievement and learning motivation. Addressing this issue, teachers' personal storytelling in learning various languages has the potential to make the learning environment more approachable and motivational. This study looks into the impact of using the teacher's personal storytelling in learning other languages on students' academic achievement and motivation. A quasi-experimental approach was adopted, with a single experimental group comprising 36 senior high school students from Indonesia. The findings show that personal storytelling greatly enhanced both academic achievement and learning motivation. Students found the strategy engaging, unique, and contextually relevant, which improved their grasp of the topics covered. Furthermore, students noted that the strategy helped them reflect on their personal language learning journeys, inspiring them to better understand English and thereby improving their academic achievement. Overall, this approach made language learning more enjoyable and vivacious. The findings indicate that personal storytelling is an excellent teaching strategy that provides a contextual, engaging, interactive, and unique approach to language acquisition. It is recommended for teachers who want to create an engaging and relevant classroom learning experience.